The Story of Non-real Man: personal identity and existentialism - R. L. Kochnev (Омский научный вестник: Серия "Общество. История. Современность")
The article analyzes the concept of personality, how it can be formulated within the framework of existential philosophy; from this perspective, the narrative theory of personality identity is criticized. An alternative description of the personality is proposed, which will be satisfactory for both analytical and existential thought